Kelembagaan Mitigasi Ekonomi: Sebuah Pendekatan Baru Sistem Penghidupan di Daerah Rawan Bencana: Economic Mitigation Institutions: A New Approach to Livelihood Systems in Disaster-Prone Areas - Eko Wahyono; Reza Amarta Prayoga; Fatwa Nurul Hakim; Nuzul Solekha; Siti Fatimah; Lis Purbandini; Djoko Puguh Wibowo; Rachmini Saparita (Society, 2023)
Research on livelihood systems tends to focus on livelihood assets, the transformation of structures, processes, and livelihood outcomes. During disasters, livelihood systems are disrupted, and various socio-economic issues may arise if not properly addressed. This research provides a perspective on social-economic mitigation institutions in the context of community livelihood systems in disaster-prone areas. The research advocates the need for economic mitigation institutions in vulnerable communities in disaster-prone regions. The framework of these economic mitigation institutions emphasizes economic commodification schemes. This research examines the institutional dynamics communities implement in economic mitigation as part of their livelihood systems in disaster-prone regions. This research adopts a qualitative constructivist approach to construct a new conceptual framework for disaster mitigation. Data is collected through in-depth interviews and focused group discussions (FGDs). The findings show that various insights provide potential solutions for disaster-prone livelihood systems based on theoretical analysis and empirical findings from disaster-prone areas in Indonesia. Economic mitigation institutions are crucial for vulnerable communities and essential for sustainable development. Moreover, communities residing in disaster-prone areas naturally develop survival strategies by utilizing available resources.